Perancangan Aplikasi E-Commerce Produk Pakaian Berbasis Andorid Menggunakan Metode Prototype pada Toko Lila Fashion - Habibika Aulia; Taufik Ramadhan; Eri Gunawan; Binniati Siregar; Henny Yustika; Angga Pratama (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
In the digital age, e-commerce applications have become a crucial component of retail business infrastructure, providing opportunities for businesses to improve marketing effectiveness, operational efficiency, and customer accessibility. Lila Fashion, a clothing store located on Batuphat Timur Street, faces operational challenges because its promotional activities still rely on conventional methods, such as physical banners, resulting in limited information dissemination and restricted market reach. This study aims to design and develop an Android-based e-commerce application system to transform conventional marketing strategies into a more adaptive, efficient, and technology-oriented business infrastructure. The data for this study were obtained through observation, interviews, and literature reviews to identify business processes, user requirements, and system development needs. The application was developed using a prototype methodology to ensure that the resulting system aligns with the expectations and needs of users through continuous feedback from the store owner and customers. The results of this study indicate that the prototype method effectively supports the development of a user-friendly interface and functional system features that meet user requirements. The developed application provides solutions for promotional cost efficiency, expands market reach, and enables customers to conduct transactions more flexibly without limitations of time and geographical location. Therefore, this Android-based e-commerce application can support the digital transformation of Lila Fashion’s business operations.